INTERACTION BETWEEN FOOD PYRAMID AND GUT MICROBIOTA. A NEW NUTRITIONAL APPROACH - Magro, Daniela O.; Rossoni, Carina; Saad-Hossne, Rogerio [UNESP]; Santos, Andrey (FapUNIFESP (SciELO), 2023)
The food pyramid is a pre-established nutritional education tool. The integration between the intestinal microbiome, food groups, and SCFA-producing bacteria, which benefit from the ingestion of these foods, has the potential to further improve and innovate healthy eating. The diet-microbiome interaction needs to be incorporated into nutrition science, and the food pyramid might assist in this interaction and nutritional learning. Against this context, this brief communication proposes through the food pyramid, the interactions between the intestinal microbiota, food groups, and SCFAs-producing bacteria.